2009
DOI: 10.4103/1319-3767.54743
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in developing countries: The burden for how long?

Abstract: Approximately 50% (over 3 billion) of the world populations are known to be infected with Helicobacter pylori, mainly in the developing countries. Among those, hundreds of millions of people develop peptic ulceration during their lifetime and still tens of millions might progress to gastric cancer. Possible modes of H. pylori transmission generally described are through direct contact between family members and also through contaminated water and food. Because the high prevalence of infection occurs mainly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
154
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 65 publications
6
154
4
5
Order By: Relevance
“…On the other hand, a study done in Mexican parents showed high H. pylori seroprevalence with low level of education (Torres et al, 1998) . This finding is consistent with the finding of studies conducted in developing countries which indicated that the most important factors influencing the transmission of H. pylori infection may differ with geographical location and study populations (Shmuely et al, 2003;Salih, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a study done in Mexican parents showed high H. pylori seroprevalence with low level of education (Torres et al, 1998) . This finding is consistent with the finding of studies conducted in developing countries which indicated that the most important factors influencing the transmission of H. pylori infection may differ with geographical location and study populations (Shmuely et al, 2003;Salih, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies were conducted on the seroprevalence and risk factors of H. pylori infection from dyspeptic patients in Ethiopia (Desta et al, 2002;Asrat et al, 2004;Tadege et al, 2005;Moges et al, 2006). However, such studies have reported inconsistent findings because the seroprevalence and risk factors of H. pylori vary with geographic location, ethnicity, and demographic factors of people both among and within populations (Salih, 2009). Therefore, there is a need for each community to determine its own prevalence and make attempts to delineate the epidemiologic factors which may be associated with the infection to eradicate H. pylori infection and apply appropriate and efficient prevention and control measures.…”
Section: Prevalence and Risk Factors Of H Pylori From Dyspeptic Patimentioning
confidence: 99%
“…Helicobacter pylori acquisition in developing countries may up to 70% compared to 40% or less in developed countries. The results may be related to improvements in hygiene conditions (10). The cag Pathogenicity Island (cag PAI) is a 40-kb DNA insertion element which encodes CagA.…”
Section: Introductionmentioning
confidence: 99%
“…It was first described in the 1980s, when it was initially identified in association with chronic gastritis and later causally linked to serious gastric pathologies such as gastric cancer and ulcers (Marshall and Warren 1984;Suerbaum and Michetti 2002). It infects .80% of humans in developing countries and, although its prevalence is lower in developed countries, nearly 50% of the worldwide human population is infected (Ghose et al 2005;Salih 2009;Salama et al 2013).Due to its clinical and evolutionary importance, there has been considerable research on mechanisms of H. pylori transmission, as well as on the population genetics and phylogenetic relationships among global isolates. Thus far, population genetic analyses have mainly focused on seven housekeeping genes (usually referred to as multilocus sequence typing or MLST), with the primary conclusions being that H. pylori strains appear highly structured, and their phylogeographic patterns correlate consistently with that of their human hosts.…”
mentioning
confidence: 99%
“…It was first described in the 1980s, when it was initially identified in association with chronic gastritis and later causally linked to serious gastric pathologies such as gastric cancer and ulcers (Marshall and Warren 1984;Suerbaum and Michetti 2002). It infects .80% of humans in developing countries and, although its prevalence is lower in developed countries, nearly 50% of the worldwide human population is infected (Ghose et al 2005;Salih 2009;Salama et al 2013).…”
mentioning
confidence: 99%